ZAKAT AS INSTRUMENTS FOR COMMUNITY ECONOMIC EMPOWERMENT IN THE NEW NORMAL ERA - Danil Saputra; Armansyah Walian; Arif Fauzan (Proceeding International Seminar of Islamic Studies, 2021)
This study's focus discusses the economic empowerment of people affected by COVID-19 in the new normal era by distributing zakat funds. This research aimed to analyze the role and function of zakat in community economic empowerment, especially those affected by the COVID-19 pandemic. This study employed a qualitative approach with interactive modeling techniques. This study's findings uncover that zakat can be one of the instruments to empower the community's economy in the new era after being affected by COVID-19.Keyword: Zakat, Community Economic Empowerment, COVID-19, New Normal Era